Question
upstudy study bank question image url

25) \( 15^{-6 p-6}-6.2=62 \)

Ask by Cummings Martin. in the United States
Feb 02,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( p = \frac{\log_{15}(5) - \log_{15}(341) - 6}{6} \)

Solution

Solve the equation \( 15^{-6p-6}-6.2=62 \). Solve the equation by following steps: - step0: Solve for \(p\): \(15^{-6p-6}-6.2=62\) - step1: Move the constant to the right side: \(15^{-6p-6}=62+6.2\) - step2: Add the numbers: \(15^{-6p-6}=68.2\) - step3: Rewrite the expression: \(15^{-6p-6}=\frac{341}{5}\) - step4: Take the logarithm of both sides: \(\log_{15}{\left(15^{-6p-6}\right)}=\log_{15}{\left(\frac{341}{5}\right)}\) - step5: Evaluate the logarithm: \(-6p-6=\log_{15}{\left(\frac{341}{5}\right)}\) - step6: Move the constant to the right side: \(-6p=\log_{15}{\left(\frac{341}{5}\right)}+6\) - step7: Change the signs: \(6p=-\log_{15}{\left(\frac{341}{5}\right)}-6\) - step8: Divide both sides: \(\frac{6p}{6}=\frac{-\log_{15}{\left(\frac{341}{5}\right)}-6}{6}\) - step9: Divide the numbers: \(p=-\frac{\log_{15}{\left(\frac{341}{5}\right)}+6}{6}\) - step10: Simplify: \(p=\frac{-\log_{15}{\left(341\right)}+\log_{15}{\left(5\right)}-6}{6}\) - step11: Simplify: \(p=\frac{\log_{15}{\left(\frac{5}{341}\right)}-6}{6}\) - step12: Evaluate: \(p=\frac{\log_{15}{\left(5\right)}-\log_{15}{\left(341\right)}-6}{6}\) The solution to the equation \(15^{-6p-6}-6.2=62\) is \(p=\frac{\log_{15}(5)-\log_{15}(341)-6}{6}\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( 15^{-6p-6} - 6.2 = 62 \), we first isolate the term involving the exponent. Adding \( 6.2 \) to both sides gives: \[ 15^{-6p-6} = 62 + 6.2 = 68.2 \] Now we can take the logarithm of both sides. Using base 10 or natural logarithm is fine, but we'll use base 10 for clarity: \[ \log(15^{-6p-6}) = \log(68.2) \] Using the power rule of logarithms: \[ (-6p - 6) \log(15) = \log(68.2) \] Now, we can solve for \( p \): \[ -6p - 6 = \frac{\log(68.2)}{\log(15)} \] Now, distributing the negative sign gives us: \[ 6p + 6 = -\frac{\log(68.2)}{\log(15)} \] Dividing every term by 6: \[ p + 1 = -\frac{\log(68.2)}{6\log(15)} \] Subtracting 1: \[ p = -\frac{\log(68.2)}{6\log(15)} - 1 \] Thus, the final simplified expression for \( p \) is: \[ p = -\frac{\log(68.2)}{6\log(15)} - 1 \] Feel free to compute the values for \( \log(68.2) \) and \( \log(15) \) to find a numerical solution for \( p \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy